Analisa Kinerja Karyawan Menggunakan Metode Skala Penilaian pada PT Industrial Multi Fan - Alan Anjar Hakim; Deny Erica (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2026)
This research aims to analyze employee performance at PT. Industrial Multi Fan using the rating scale method as a structured performance appraisal approach. The rating scale method is applied to measure employee work achievement based on several key criteria, including communication skills, teamwork, quality of work, initiative, time efficiency, and employee satisfaction. Data were collected through direct observation and the distribution of questionnaires to 30 employees selected as research respondents. The results of the study indicate that the majority of employees fall into the “good” performance category, reflecting satisfactory levels of communication, cooperation, and work quality. However, the findings also reveal certain weaknesses, particularly in the aspects of employee initiative and time management efficiency, which require further attention. These results provide valuable input for management in conducting performance evaluations and formulating more targeted and effective employee development programs. Through objective, systematic, and continuous performance assessments, the company is expected to enhance individual employee performance, strengthen teamwork, and ultimately improve overall organizational effectiveness and productivity.